2018
DOI: 10.1016/j.aott.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Tourniquet pressure settings based on limb occlusion pressure determination or arterial occlusion pressure estimation in total knee arthroplasty? A prospective, randomized, double blind trial

Abstract: ObjectiveThe aim of this study was to compare the limb occlusion pressure (LOP) determination and arterial occlusion pressure (AOP) estimation methods for tourniquet pressure setting in adult patients undergoing knee arthroplasty under combined spinal-epidural anesthesia.MethodsNinety-three patients were randomized into two groups. Pneumatic tourniquet inflation pressures were adjusted based either on LOP determination or AOP estimation in Group 1 (46 patients, 38 female and 8 male; mean age: 67.71 ± 9.17) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
(71 reference statements)
2
21
1
2
Order By: Relevance
“…Although there are some fluctuations in the curves of f blood and StO 2 which are likely caused by motion artifacts, f blood and StO 2 during the occlusions apparently deviated from the baseline and the deviations were much larger than standard deviations during the baselines. The decreases in StO2 during both occlusions are similar to results reported in previous studies [33,[37][38][39][40], and are expected because tissue consumes oxygen and no oxygenated blood is supplied under the occlusions. We observed that f blood decreased slightly during both arterial and venous occlusions, which are not in agreement with trends often reported [33,[35][36][37]40].…”
Section: In-vivo Cuff Occlusion Experiments Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Although there are some fluctuations in the curves of f blood and StO 2 which are likely caused by motion artifacts, f blood and StO 2 during the occlusions apparently deviated from the baseline and the deviations were much larger than standard deviations during the baselines. The decreases in StO2 during both occlusions are similar to results reported in previous studies [33,[37][38][39][40], and are expected because tissue consumes oxygen and no oxygenated blood is supplied under the occlusions. We observed that f blood decreased slightly during both arterial and venous occlusions, which are not in agreement with trends often reported [33,[35][36][37]40].…”
Section: In-vivo Cuff Occlusion Experiments Resultssupporting
confidence: 89%
“…Venous occlusion was achieved by applying pressure that approximately equaled to the average of the systolic and diastolic blood pressures of the volunteer. Arterial occlusion was achieved by applying pressure about 50 mmHg higher than the systolic blood pressure of the volunteer to ensure total occlusion of the blood flow [38].…”
Section: In Vivo Cuff Occlusion Experiments and Calibration Of Spectramentioning
confidence: 99%
“…The damage to both skeletal muscles and internal organs caused by local ischemiareperfusion injury (IRI) is mostly present as a result of intraoperative use of tourniquet for temporary stop of blood circulation in internal organs or for stop of blood loss from the limb [1][2][3][4][5][6][7][8][9][10]. Primary damage leads to mechanical pressure, as for secondary mechanismsreactive oxygen intermediates and lipid peroxidation are responsible for it [11].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods are used nowadays in therapeutic treatment: from lowering the temperature of the limb to the use of various drugs. Thus, the protective effect of curcumin on the myocardium, kidneys, nervous tissue and lung has been proved in cases of this pathology [26][27][28][29]; montelucast reduces the level of local and systemic manifestations [29], legalon, thiotriazolin, emoxipine, silymarin have antioxidant effect [3][4][5][6][7][8][9][25][26][27][28][29][30]. Studying of changes in the activity of antioxidant enzymes is needed for prediction of the effect of a specific antioxidant corrector.…”
Section: Introductionmentioning
confidence: 99%
“…Постановка проблеми і аналіз останніх досліджень та публікацій. Ушкодження як скелетних м'язів, так і внутрішніх органів на тлі локальних процесів ішемії-реперфузії з метою зупинки кровотечі з ураженої кінцівки чи інтраопераційно вивчаються давно [1][2][3][4][5][6][7][8][9][10]. Механічний тиск від гемостатичного джгута створює первинне ушкодження м'яких тканин, судин та нервів.…”
unclassified